KONTRADIKSI SIMBOL DAN SUBSTANSI NILAI ISLAM DALAM ARSITEKTUR MASJID - Yulia Eka Putrie (lp2m-uin malang, 2010)
Grand mosques are commonly designed as a symbol of the glory of Islam. Many symbolic elements and forms are also included in these mosques. Consequently, these kind of mosques are usually built in a very luxurious and monumental way. In contrary, there are some values of Islam which unfortunately have been forgotten while building them. This research aims to identified contradictions that take place between those symbols and the substances of Islamic values in some mosques’ architecture. Furthermore, this research also aims to find the reasons behind those contradictions. The method that used in this research is the normative criticism where a standard or a principle is used to assess the quality or success of a building or urban setting. The principle that used as the parameter in this research is some Islamic values which are related directly to mosque architecture, such as moderation, openness, equality, advantageousness, and prevention of dangers (mudharat). The results of this research are (1) monumentality as the symbol of Islamic glory is oftenly found contradicted to most Islamic values, and (2) Islamic values which mostly forgotten while designing a symbolic-based mosques architecture are moderation, advantageousness, and prevention of dangers. Moreover, the reasons behind these contradictions are (1) conceptual problems in the owners’ and architects’ mind while representing the symbol of Islamic glory in buildings, (2) operational problems in architects’ ways of representing symbol in some un-Islamic architectural designs.